Sistema de detección de metano producido por bovinos (2021)
This document aims to show the process of design and assembly of an embedded system able to monitor continuously the production (volume) of methane by cattle over a full day (24 hours). This system is a low-cost prototype that can be easily and quickly replicated. It is also not invasive for the cattle nor does it cause any discomfort, although the animal must be accustomed before putting the device on for a period of 15 days. In order to be able to monitor several animals at the same time, the device is designed to connect via a Wi-Fi network to a local server, which allows the use of as many devices as necessary, with the data being handled and received through a graphic interface deployed on the server.